2020
DOI: 10.3390/su122310174
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Strategic Benchmarking of Intellectual Capital Management in Logistics Service Providers

Abstract: This research developed a new integrated method for addressing the deficiencies and gaps generally found in past studies on benchmarking and for benchmarking intellectual capital (IC) in the underdeveloped domain of logistics. To resolve the lack of consideration of relationships among past benchmarking concepts and the impacts of their managerial factors, as well as to examine the wide range of elements and indicators of IC influencing the sustainable development of organizations, the proposed approach integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Multi-Criteria Decision-Making (MCDM) techniques are often adopted to solve complex problems based on experts' judgment. Previous studies have shown that MCDM methods, combined with a fuzzy set theory or other methods [35,36], can result in more reliable results. Several studies have used this approach in the areas of health [37], safety [38] and environment [39], and economy [40] for identifying and classifying relationships among variables.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…Multi-Criteria Decision-Making (MCDM) techniques are often adopted to solve complex problems based on experts' judgment. Previous studies have shown that MCDM methods, combined with a fuzzy set theory or other methods [35,36], can result in more reliable results. Several studies have used this approach in the areas of health [37], safety [38] and environment [39], and economy [40] for identifying and classifying relationships among variables.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…The general risk management includes eliminating the uncertainty of investment business and financing, implementing diversification to hedge investment risks, coping with the possible situations, etc., which constitute the content of risk management. However, once the international logistics risk occurs, it will lead to huge losses, therefore, the goal of international logistics risk management is to go beyond the prevention of unpredictable risks, grasp the unpredictable situation as far as possible in advance, minimize the damage when risks occur, and minimize the impact on commercial activities [9]. Its purpose is to predict and prevent the problems that occur or may occur in logistics activities, rather than management after they occur.…”
Section: Literature Reviewmentioning
confidence: 99%
“…AHP is the most common MCDM method in risk assessment, and most previous studies used AHP to evaluate risk factors. AHP only considers the linear association between different hierarchies but ignores the interdependence between indicators, which exists with certain limitations and deviations [24,25].…”
Section: The Analytic Network Processmentioning
confidence: 99%